Legal Protection for Children from the Impact of Violence in Online Games - Handayani, Tri Astuti; Mangar, Irma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
Digital games offer fast and wide access, even allowing players from different countries to connect with each other. Purchasing goods or services in the game is relatively easy and can be done from anywhere. Due to the ease of access and support for internet connections, digital games are now more popular than traditional games, especially by children. This research is normative research Normative law research has a tendency to image law as a prescriptive discipline where only looking at law from the perspective of its norms which of course is descriptive, this research is carried out in real conditions with the aim of being able to find existing facts to be used as data fillers in this research so that later the point of solving the problem will also be found. That in accordance with the mandate of the law, children who are victims of violence have the right to protection. This research is seen as very important to be carried out. Although a number of previous studies have discussed legal protection for children as victims of pornography crimes, the authors feel the need to conduct a more in-depth study regarding legal protection for children from the impact of violence in online games. This focus is expected to make a new and relevant contribution to child protection efforts in the digital era.